Cyber Crime Protection Law in Indonesia on the Risk of Loss of Binary Option - Anggun Rahmawati; Danang Sugihardana; Feri Budi Lestanto; Nuriyyah Nailis Sha'adah; Rafi Arnanda Faturohman; Tasya Resti Fauziah (Proceeding International Conference Restructuring and Transforming Law, 2022)
Advances in science and technology have resulted in the advancement of trading methods which are currently not only done conventionally, but also through virtual global.Through commerce in cyberspace, anyone, anywhere, can reach any object. This includes investing activities that are very profitable financially, and are also activities that have a high risk. Investing or investing exclusively or not, with the hope of getting the maximum profit in a certain period of time from the investment results.Technological developments, supported by the abundance of supply and demand, have created a binary options platform.Binary options are online trading instruments that offer investment by choosing the assets to trade, generally in the form of currencies, stock indices, cryptocurrencies, to commodities.We compiled this study using a normative legal approach in the form of a statutory approach and a conceptual approach. Technological developments do not always have a positive impact on financial investment products.This study emphasizes that binary options is not a commodity futures trading activity or investment. Binary options trading is illegal in Indonesia because it has not been licensed and its legality is not recognized by laws and regulations. Without a license, there is no clarity on consumer protection in binary options, both legally and practically.This research leads to the emphasis on legal science by examining the legal rules used and applicable to the community to be studied and researched. Cybersecurity laws and regulations in Indonesia divide responsibilities into several ministries and are considered ineffective in preventing cyber threats and crimes. Therefore, a comprehensive cyber security regulation is needed in Indonesia.